Formulasi campuran olein minyak sawit untuk memproduksi shortening bebas lemak trans [Formulation of palm oil olein mixture to produce trans-fat-free shortening] - Mursalin, Mursalin; Yernisa, Yernisa; Hizazi, Achmad (Jurnal Teknologi & Industri Hasil Pertanian, 2024)
Shortening is a solid fat with the functional properties needed to produce a better texture and appearance for bakery or confectionery products, as well as frying and cooking media. Shortening is made by mixing two or more vegetable oils and then modifying them through a chemical or enzymatic interesterification process. In this research, the raw material for shortening was prepared from a mixture of 2 types of palm oil olein: refined olein (ROL) and mid olein (MOL). This research aimed to determine the optimal ROL and MOL mixture ratio in the chemical interesterification process, which produces shortening with the best quality and specifications. Five levels of ROL/MOL comparison consisting of (100/0), (95/5), (90/10), (85/15), and (80/20) were chemically inter-esterified using a sodium methoxide catalyst under a vacuum of 0.8 bar at a temperature of 110 oC and speed of 500 rpm. The results showed that the increase of MOL in the ROL/MOL formulation tends to increase the shortening melting point. However, increasing MOL did not change the iodine value, and all the ROL/MOL ratios produced shortening with specifications that met the SNI 3718:2018 requirement, and the best ROL/MOL ratio was 80/20.